PENDEKATAN FILOLOGI EDWAR DJAMARIS DAN CHARLES J. ADAMS DALAM KAJIAN ISLAM PENUH RAHMAT - Khafifatul Fian; Ali Muhdi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
This study aims to comprehensively analyze philological approach perspectives of Edwar Djamaris and Charles J. Adams, how the history of the development manuscript studies and philological science, and how the implementation of philological approaches in Islamic studies. The type of research used is literature review through data collection techniques by searching for sources from books or articles that researchers analyze descriptively analytically.  The results showed that the proximity philology according to Edwar Djamaris in terms of concept or term is almost the same as described by Charles J. Adams, except that in his review it can be said to be slightly different.  Edwar Djamaris is more about philology that is literary in nature or ancestral heritage, while Charles J. Adams is more about texts containing Islamic teachings. The historical development of manuscript studies and philological science is divided into five periods: the Iskandariah, Roman, Renaissance, Middle Eastern, and Indian Schools. The application of the philological approach in   Islamic studies is found in the interpretation sources of Islamic law, as the researcher explained regarding the interpretation of the Quran Surat Lukman: 17 and implementation in terms of the relationship between philological studies and Islamic studies rahmatan lil'alamin.